2014
DOI: 10.1177/0148607114540214
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Critical Illness on Triglyceride Absorption

Abstract: Small intestinal absorption of lipid is diminished during critical illness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 46 publications
0
30
0
2
Order By: Relevance
“…On the other hand, fat maldigestion and malabsorption turned out to be more remarkable in critically ill patients in recent studies. Ali Abdelhamid and colleagues 16 infused a liquid nutrient containing 13 C‐triolein and 3‐O‐methylglucose (3‐OMG) directly into the duodenum of critically ill patients and healthy volunteers, and then they measured the exhaled 13 CO 2 and serum 3‐OMG concentrations and found that the lipid absorption in the small intestine was markedly reduced in critically ill patients compared with healthy volunteers. Taurine and carnitine, which are essential nutrients for fat digestion and absorption, were at lower levels in critically ill patients than in healthy subjects 17 , 18 .…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, fat maldigestion and malabsorption turned out to be more remarkable in critically ill patients in recent studies. Ali Abdelhamid and colleagues 16 infused a liquid nutrient containing 13 C‐triolein and 3‐O‐methylglucose (3‐OMG) directly into the duodenum of critically ill patients and healthy volunteers, and then they measured the exhaled 13 CO 2 and serum 3‐OMG concentrations and found that the lipid absorption in the small intestine was markedly reduced in critically ill patients compared with healthy volunteers. Taurine and carnitine, which are essential nutrients for fat digestion and absorption, were at lower levels in critically ill patients than in healthy subjects 17 , 18 .…”
Section: Introductionmentioning
confidence: 99%
“…AEèð ìîaeíà ñïîaeèâàòè åíòåðàëüíî àáî ïàðåíòåðàëüíî, ³, ÿê ³ ó âèïàäêó âóãëåâîä³â, òî÷íà íåîáõ³äíà ê³ëüê³ñòü íåâ³äîìà. Ïðè êðèòè÷íîìó çàõâîðþâàíí³ ïîðóøóºòüñÿ âñìîêòóâàííÿ aeèðó [193]. Ïðè êðèòè÷íîìó çàõâîðþâàíí³ ìåòàáîë³çì ë³ï³ä³â çì³íþºòüñÿ, à íèçüêèé ð³âåíü òðèãë³öåðèä³â ³ âèñîêèé ð³âåíü õîëåñòåðèíó (ËÏÂÙ) â ïëàçì³ êðîâ³ ïîâ'ÿçàí³ ç ïîêðàùåííÿì âèaeèâàíîñò³ [194].…”
Section: êîìåíòàð äî ðåêîìåíäàö³é 23-25unclassified
“…The endoluminal cleavage of triglycerides in food and those incorporated in nutrition formulas for enteral gastric lipase turns them into diglycerides and free fatty acids (FFAs). As for carbohydrates, the absorption of fat from the GI tract is altered in critically ill patients: a recent study showed a 50% reduction in the absorption of long‐chain fatty acids in mechanically ventilated critically ill patients compared with healthy controls 50 . A second cleavage by pancreatic lipase converts them into monoglycerides and fatty acids.…”
Section: Clinical Consequencesmentioning
confidence: 99%